Effect of complex training on lower limb strength and running economy in adolescent distance runners - Yu, Shiping; Zhou, Shengqing; Peng, Daibin; Jie, Dongli (Frontiers in Physiology, 2025)
BackgroundWhile traditional resistance training has been widely used in distance running training, the effects of complex training combining heavy resistance and plyometric exercises on adolescent runners remain unclear. Understanding the impact of complex training on running economy and lower limb strength could provide valuable insights for optimizing training programs for young athletes.PurposeTo examine the effects of an 8-week complex training program on lower limb strength and running economy in adolescent distance runners compared to traditional resistance training.MethodsThirty-two male adolescent distance runners (age: 16.75 ± 0.68 years) were randomly assigned to either a complex training group (CT; n = 16) or a resistance training group (RT; n = 16). Both groups completed their respective training programs three times per week for 8 weeks, in addition to their regular endurance training. Running economy at three speeds (12, 14, and 16 km/h), maximal oxygen uptake (VO2max), blood lactate concentration, One-repetition maximum (1RM) squat strength, countermovement jump (CMJ), squat jump (SJ), drop jump (DJ), and reactive strength index (RSI) were assessed before and after the intervention.ResultsThe CT group showed significantly greater improvements in running economy at all speeds (p < 0.001) compared to the RT group. Both groups demonstrated significant improvements in 1RM squat strength (CT: p < 0.001; RT: p < 0.001), CMJ (CT: p < 0.001; RT: p < 0.001), and SJ (CT: p = 0.005; RT: p < 0.001). The CT group exhibited superior improvements in CMJ peak power (p = 0.010), DJ performance (p = 0.017), and RSI (p < 0.001). Blood lactate concentrations at submaximal speeds decreased significantly more in the CT group compared to the RT group (p < 0.05).ConclusionComplex training appears to be more effective than traditional resistance training for improving both running economy and power-related performance measures in adolescent distance runners. The combination of heavy resistance and plyometric exercises may provide superior neuromuscular adaptations that enhance both strength and running efficiency.